Jornadas alternativas: o ensino religiosos e o movimento Nova Era - Teixeira, Talita Bender (2011)
The present study consists in an analysis about New Age movement and Religious Education, optional subjects at Brazilian public schools. The intersection Between these two themes happens in theorical and contextual studies through the observation of environment religious diversity, religious phenomenon in which the theme occurs as problematical for the Theology and Religions Sciences researcher. The fundamental issue I try to understand whether it is possible to include the New Age theme in the school curriculum or if this process already takes place in practice, since the New Age comes from personal constructions based on self reflexivity.